PEMBELAJARAN SOSIAL ORANG TUA DALAM MENDAMPINGI ANAK SEKOLAH MINGGU DI GEREJA KRISTEN JAWA PETORAN SURAKARTA - Agustiana, Nova; Juntak, Justin Niaga Siman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study aims to analyze the influence of parents’ social learning experiences on their parenting styles in accompanying their children in Sunday School, and to identify the main factors that contribute to the lack of parental involvement in these religious activities. The research uses a qualitative approach with a case study method. The informants include three parents and two Sunday School teachers at the Gereja Kristen Jawa (GKJ) Petoran Surakarta. Data were collected through in-depth interviews and observation. The findings reveal that parents' past experiences of spiritual learning significantly influence how they guide their children’s faith development. Parents who received religious education during childhood tend to understand the importance of involvement in their children's spiritual lives, although time constraints and work obligations often hinder direct participation. Conversely, parents without early Christian formation often rely entirely on the church for their children’s religious education. Sunday School teachers observed that the lack of parental involvement negatively impacts the children's discipline and motivation in participating in religious activities. These findings align with Albert Bandura's social learning theory, which emphasizes the importance of modeling, reinforcement, and observation in the learning process. Children learn not only through verbal instruction but also by imitating significant figures in their environment, especially their parents. Therefore, active parental involvement plays a critical role in fostering the children’s engagement and spiritual growth in Sunday School. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh pengalaman pembelajaran sosial orang tua terhadap pola asuh mereka dalam mendampingi anak-anak di Sekolah Minggu, serta mengidentifikasi faktor-faktor utama yang menyebabkan kurangnya keterlibatan orang tua dalam kegiatan tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Informan terdiri dari tiga orang tua dan dua guru Sekolah Minggu di Gereja Kristen Jawa Petoran Surakarta. Teknik pengumpulan data dilakukan melalui wawancara mendalam dan observasi. Hasil penelitian menunjukkan bahwa pengalaman pembelajaran sosial yang diperoleh orang tua pada masa kecil sangat mempengaruhi cara mereka membimbing anak dalam kehidupan rohani. Orang tua yang memiliki latar belakang pembelajaran iman cenderung lebih memahami pentingnya pendampingan, meskipun keterbatasan waktu dan pekerjaan seringkali menjadi kendala utama. Sementara itu, orang tua yang tidak memiliki pengalaman rohani sejak kecil cenderung menyerahkan pembinaan anak sepenuhnya kepada gereja. Guru Sekolah Minggu mengamati bahwa kurangnya keterlibatan orang tua berdampak pada kedisiplinan dan motivasi anak dalam kegiatan rohani. Temuan ini selaras dengan teori pembelajaran sosial Albert Bandura, yang menekankan pentingnya modeling (keteladanan), penguatan, dan observasi dalam proses belajar. Anak-anak belajar bukan hanya dari pengajaran verbal, tetapi juga dari meniru perilaku signifikan di sekitar mereka, terutama orang tua. Oleh karena itu, keterlibatan orang tua secara aktif menjadi faktor penting dalam membentuk keaktifan dan pertumbuhan iman anak di Sekolah Minggu.